Sizing up (K1−xNax)NbO3 films: a review of synthesis routes, properties & applications. (19th April 2021) - Burns, Stuart R.; Dolgos, Michelle R.
Abstract : This review discusses (K, Na)NbO3 thin films, with a focus on synthesis, chemically modifying properties, plus piezoelectric and biomedical KNN devices. Abstract : Potassium sodium niobate, (K1− x Na x NbO3, KNN), is often discussed in the realm of lead-free piezoelectrics due to the widespread restrictions on the use of hazardous lead in electronics. However, as PbZr1− x Ti x O3 (PZT) is by far the best performing piezoelectric for sensors, actuators and other industry applications, it is somewhat difficult to envision a lead-free alternative. KNN does offer other benefits over archetypical piezoelectrics, such as biocompatibility and easily tunable phase transition temperatures, which will soon be utilized in new device applications. In this review, we will discuss KNN thin films and the techniques used to synthesize them. We will discuss how properties are tailored through additivities and review future applications in which KNN thin films are leading the way. We will also consider the environmental impact of this material, and finally the role which chemists can play in developing KNN thin films in the near future.